2022
DOI: 10.1371/journal.pone.0271563
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical improvement of regional tissue oxygenation after packed red blood cell transfusion

Abstract: Background It is well established that counter-regulation to hypoxia follows a hierarchical pattern, with brain-sparing in preference to peripheral tissues. In contrast, it is unknown if the same hierarchical sequence applies to recovery from hypoxia after correction of anemia with packed red blood cell transfusion (PRBCT). Objective To understand the chronology of cerebral and splanchnic tissue oxygenation resulting after correction of anemia by PRBCT in preterm infants using near-infrared spectroscopy (NIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Nature and volume of feeding and total fluid intake remained unaltered during the entire study period. A detailed protocol has also been published elsewhere 19–21 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nature and volume of feeding and total fluid intake remained unaltered during the entire study period. A detailed protocol has also been published elsewhere 19–21 …”
Section: Methodsmentioning
confidence: 99%
“…The data recording extended from at least 4 h before the beginning of PRBCT until 24 h after its completion. SpO 2 was used along with StO 2 to calculate fractional tissue oxygen extraction for other related publications from the same study 19–21 . SCOR (also called CSOR, cerebro‐splanchnic oxygenation ratio 3 ; MCOR, mesenteric‐cerebral oxygenation ratio 15 ) was calculated by a continuous prospective evaluation of StO 2 c and StO 2 s. StO 2 was evaluated using a four‐wavelength NIRS cerebral and splanchnic tissue monitor (FORE‐SIGHT® absolute cerebral oximeter, CASMED, Branford, Connecticut, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Balegar et al (79) conducted a prospective cohort study to see if this sequence also occurs in response to anaemia which is treated with a RBCT in a small cohort of preterm infants born at less than 32 weeks gestational age and with a birthweight of less than 1500g. They completed pre transfusion cerebral and splanchnic FTOE with hourly means for 24 hours after RBCT and reported that cerebral FTOE significantly decreased during and for 24 hours after RBCT demonstrating improved cerebral oxygenation, but they found no significant changes in splanchnic FTOE.…”
Section: Effect Of Hb and Rcbt On Gut Oxygenationmentioning
confidence: 99%